From uranium(IV) oxalate to sintered UO2: Consequences of the powders' thermal history on the microstructure. Issue 16 (December 2015) - Martinez, J.; Clavier, N.; Ducasse, T.; Mesbah, A.; Audubert, F.; Corso, B.; Vigier, N.; Dacheux, N.
Abstract: Wet chemistry methods involving the initial precipitation of crystallized precursors are frequently reported as a promising way to prepare actinide oxides. Sintering of UO2 powders prepared from uranium(IV) oxalate dihydrate was thus investigated in order to point out the influence of various parameters inherited from the conversion step leading from the precursor to the final oxide. In this perspective, different thermal cycles were considered, based on strictly reducing conditions, or on the successive use of oxidizing/reducing atmospheres. The modifications underwent by the samples during the conversion step were then investigated in terms of crystal structure, morphology and associated specific surface area, as well as residual carbon content. The role of these parameters in the development of sintered UO2 microstructure was also examined, specially emphasizing the potential role of the residual carbon content over the final density.